1987
DOI: 10.2118/87-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Temperature On Heavy Oil-Water Relative Permeability Of Sand

Abstract: HEAVY OIL Effects of temperature on heavy oil-water relative permeability of sand BRIJ B. MAINI Petroleum Recovery Institute and T. OKAZAWA Esso Resources Canada Limited ABSTRACT Although a number of studies have reported significant effects of temperature on relative permeabilities no consensus has emerged on the generality of such effects nor on possible mechanisms causing such effects. Some of the recent studies have found relative permeability to be independent of temperature and have suggested that most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…The relative permeabilities we obtained for dolomite rocks showed a similar trend as those reported by Maini and Okazawa (1987) for sandstone and heavy oil systems (Fig. 16).…”
Section: Experiments Set #2 Mn-x-py (Heavy Oil)supporting
confidence: 86%
See 1 more Smart Citation
“…The relative permeabilities we obtained for dolomite rocks showed a similar trend as those reported by Maini and Okazawa (1987) for sandstone and heavy oil systems (Fig. 16).…”
Section: Experiments Set #2 Mn-x-py (Heavy Oil)supporting
confidence: 86%
“…The effect of temperature gradient on relative permeability measurement was studied by Watson and Ertekin (1988). Maini and Okazawa (1987) analyzed the unsteadystate experiments conducted on unconsolidated silica sand using Bodo stock tank oil and by history matching technique. They concluded that the obtained relative permeability increased with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Davidson (1969) has indicated the effect of temperature on the relative permeability, while not mentioning anything about the end point saturations. Maini and Okazawa (1987) have considered fixed end point saturations and have confirmed the change in k r values with temperature. Schembre et al (2006) have proposed that the rock becomes more water wet at higher temperatures and that affects the relative permeability curves.…”
mentioning
confidence: 71%
“…Polikar et al (1990) also stated that it is not possible to predict theoretically what the effect of temperature on relative permeabilities could be, and the results are system specific. Maini and Okazawa (1987) have also concluded that due to several artifacts involved in the experiments no effect of temperature could be justified.…”
Section: Resultsmentioning
confidence: 99%
“…A published simulation study has shown that recovery will increase as ratio of µo/µw gets lower (Maini and Okazawa, 1987). The outcome of this research shows that brine viscosity reduction is not as drastic as oil, from 0.55 to 0.47 cP and from 68 to 46 cP, for brine and oil respectively.…”
Section: Well and Inflow Performancementioning
confidence: 67%